2020
DOI: 10.1097/mao.0000000000002460
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Scalar Shift and Insertion Depth in Human Cochlear Implantation

Abstract: Objective: The intracochlear position of an electrode array may influence the outcome after cochlear implantation. The design of the electrode array can increase the risk of trauma causing penetration of the basilar membrane or shift of the electrode array into the scala vestibuli. The aim of the present study was to identify a scalar shift after implantation of two different electrode arrays developed by one manufacturer. Study Design: Retrospective an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…Four out of the six studies comparing speech perception scores between STL and non-STL reported postoperative means (see Table III), and were, therefore, included. 5,20,32,37 These studies evaluated mainly PM arrays, with time of testing ranging between 3 and 18 months. In addition, three types of lists were used; the CNC words, AzBio sentences, or the Freiburger monosyllables (FMS).…”
Section: Data Extractionmentioning
confidence: 99%
“…Four out of the six studies comparing speech perception scores between STL and non-STL reported postoperative means (see Table III), and were, therefore, included. 5,20,32,37 These studies evaluated mainly PM arrays, with time of testing ranging between 3 and 18 months. In addition, three types of lists were used; the CNC words, AzBio sentences, or the Freiburger monosyllables (FMS).…”
Section: Data Extractionmentioning
confidence: 99%
“…The mean insertion force of MSE is less than 10 mN, corresponding to about 10% of the force expected for a normal straight electrode array with a similar insertion depth [ 34 ]. The MSE has a lower probability of dislocation into the scala vestibuli (scalar shift) than lateral or perimodiolar electrode arrays [ 35 , 36 ]. The functional advantages of the mid-scalar position are lower electrical thresholds, higher dynamic ranges and lower channel interaction compared to electrodes that are usually placed more peripherally in the Scala tympani [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although an important concern during array insertion is to decrease intracochlear trauma, previous studies have reported such deleterious events with all types of arrays [Finley et al, 2008;Boyer et al, 2015;Wanna et al, 2015;O'Connell et al, 2016;Dees et al, 2018;Riggs et al, 2019;Zelener et al, 2020;Daoudi et al, 2021;Vittoria et al, 2021]. Intracochlear trauma is associated with both decreased hearing performance in patients and loss of residual hearing in the case of hearing preservation attempts [Wanna et al, 2011].…”
Section: Introductionmentioning
confidence: 99%